Rehabilitation of the handicapped child - Who cares for the caregiver? - Seyi L. Amosun; Benson A. Ikuesan; lyabo J. Oloyede (South African Journal of Physiotherapy, 1996)
The mental health of caregivers of handicapped children (n=68), and of caregivers of children with minor ailments (n=40), was assessed using the General Health Questionnaire (GHQ). In the cross-sectional study, the caregivers of handicapped children had a significantly higher mean score which was above the threshold score. This suggests that the task of caring for disabled children may have a stressful impact on the caregivers which may contribute to psychiatric morbidity. There is a need to periodically assess the mental health of the caregiver, even as the rehabilitation of the handicapped child progresses. Addressing the psychological disturbances in the caregiver should form part of the treatment of the handicapped child.